Green Design as an Approach to the Urban Coordination and Environmental Sustainability (Al-Academy, 2025)
In light of the increasing and unprecedented environmental challenges the world is facing, such as climate change, depletion of Natural Resources, increasing population density and harmful industrial practices, it is imperative to think and search for new solutions that help reduce these problems and provide a better quality and sustainable life, hence the role of green design emerges as a new entrance and an innovative solution, combining environmental sustainability and aesthetic as an essential pillar in the operations of This design approach seeks to transform outdoor spaces into beautiful, healthy and nature-friendly places to achieve environmental sustainability, hence the importance of this research through the use of plant elements with their color, shape and texture characteristics as inputs to the design process to produce innovative and environmentally friendly wall configurations, it does not represent just an aesthetic or artistic orientation, but constitutes an integrated philosophy aimed at achieving a delicate balance between aesthetics and environmental efficiency, therefore green design is an integrated approach linking function, beauty and sustainability, and thus the current research aims to activate the role of design Green Sustainability To achieve the research goal and solve its problem, which is how to take advantage of green design to achieve urban coordination and environmental sustainability, the researcher will follow the descriptive analytical approach.